INDENTIFIKASI SISWA BERPRESTASI DI BAWAH KEMAMPUAN (UNDERACHIEVEMENT) SEKOLAH DASAR DI KOTA MATARAM - A. Hari Witono; Muhammad Tahir; Heri Setiawan (Universitas Trilogi, 2021)
The general purpose of this research is to obtain a picture of underachievement students in elementary school in Mataram city (Case Study in Grade VI SD Negeri 41 Mataram). This research uses qualitative type with case study approach. This research was conducted at SDN 41 Mataram, especially grade VI A and VI B. The subject of this research was grade 6 students at SD 41 Mataram. The object of this research is the achievement under the ability (underachievement) of the students that occurred in the case of grade 6 SDN Mataram. Data is collected using observation methods, interviews, and documentation. Researchers act as instruments of research as well as data collection. Data analyzed with Miles and Huberman models are data reduction, display data, and conclusion drawing / verification. Based on the data collection procedure carried out, the subject of this study obtained 4 underachiever students (2 students sitting in Via class and 2 people in Vib class namely Elan, Praja, Gede Loka, Nengah Loki. The results showed that the characteristics that appear in underachievement students are: (a) negative perception of self-ability; (b) a desire for low achievement; (c) external locus control (blaming something outside); (d) do not persevere during the teaching and learning process. (e) nosy and unable to sit quietly during the teaching and learning process; and (f) apathy towards the Subject. The causes of problems in underachievement children are (a) the learning system in schools; (b) negative teacher perception factor (labelling); and (c) family and home environment factor.